Validity and Reliability of the MyJump 2 Application for Measuring Vertical Jump in Youth Soccer Players Across Age Groups - Andreas Stafylidis; Yiannis Michailidis; Athanasios Mandroukas; Ioannis Metaxas; Konstantinos Chatzinikolaou; Charalampos Stafylidis; Sophia D. Papadopoulou; Thomas I. Metaxas (Applied Sciences)
The aim of this study was to assess the validity and intra-session reliability of the MyJump 2 smartphone application for evaluating countermovement jump (CMJ) and squat jump (SJ) performance in youth soccer players using the Chronojump contact mat system as a reference. Twenty-one male soccer players from an elite team (U14–U19) were randomly selected to participate in countermovement jump (CMJ) and squat jump (SJ) assessments, with jump heights recorded simultaneously by both systems. Validity was examined through Bland–Altman analysis, Pearson and Spearman correlations and linear regression. Reliability was assessed using intraclass correlation coefficients (ICC), standard error of measurement (SEM) and Bland–Altman test–retest analysis. Results revealed minor systematic overestimation by MyJump 2 (+0.943 cm for CMJ; +1.042 cm for SJ). Strong correlations were found between MyJump 2 and Chronojump (r = 0.972 for CMJ; r = 0.955 for SJ), while ICCs exceeded 0.97 for both jump types, indicating excellent reliability. These findings support MyJump 2 as a valid and reliable alternative for vertical jump testing in adolescent and junior soccer players as an accessible and suitable tool for field-based performance monitoring regarding vertical jumping ability.